Is the national health insurance scheme a pathway to sustained access to medicines in Nigeria? - Nkolika Uguru; Udochukwu Ogu; Chibuzo Uguru; Ogochukwu Ibe (BMC, 2024)
Abstract Objective The debate surrounding access to medicines in Nigeria has become increasingly necessary due to the high cost of essential medicine drugs and the prevalence of counterfeit medicines in the country. The Nigerian government has proposed the implementation of the National Health Insurance Scheme (NHIS) to address these issues and guarantee universal access to essential medicines. Access was investigated using the 3 A's (accessibility, affordability, and availability). This paper investigates whether the NHIS is a viable pathway to sustained access to medicines in Nigeria. Design This was a cross-sectional study using a mixed-methods design. Both qualitative and quantitative methods were utilized for the study. Setting This study was conducted at NHIS-accredited public and private facilities in Enugu State. Participants 296 randomly selected enrollees took part in the quantitative component, while, 6 participants were purposively selected for the qualitative component, where in-depth interviews (IDIs) were conducted face-to-face with NHIS desk officers in selected public and private health facilities. Results The quantitative findings showed that 94.9% of respondents sought medical help. Our data shows that 78.4% of the respondents indicated that the scheme improved their access to care (accessibility, affordability, and availability). The qualitative results from the NHIS desk officers showed that respondents across all the socio-economic groups reported that the NHIS had marginally improved access to medicine over the years. It was also observed that most of the staff in NHIS-accredited facilities were not adequately trained on the scheme's requirements and that most times, essential drugs were not readily available at the accredited facilities. Conclusion The study findings revealed that although the NHIS has successfully expanded access to medicines, there remain several challenges to its effective implementation and sustainability. Additionally, the scheme's coverage of essential medicines is could be improved even more, leading to reduced access to needed drugs for many Nigerians. A focus on the 3As for the scheme means that all facility categories (private and public) and their interests (where necessary) must be considered in further planning of the scheme to ensure that things work out well.